Effects of a low-center-of-gravity backpack on the trunk stability of mountaineers while ascending and descending - Yoo, Won-gyu (J Phys Ther Sci, 2015)
[Purpose] This study developed a backpack with a low center of gravity (LCG) and investigated the effects of the LCG backpack on the trunk stability of mountaineers while ascending and descending. [Subjects and Methods] Ten males aged 20–32 years were recruited. The subjects ascended and descended a road with an inclination of 30 degrees wearing the standard or LCG backpack, and trunk acceleration was measured using a tri-axial accelerometer. [Results] The anterior-posterior (AP) and medial-lateral (ML) trunk acceleration while ascending and descending with the LCG backpack were significantly lower than those with the standard backpack. [Conclusion] The results suggest that the LCG backpack could prevent falling injuries during mountaineering and mountain-related activities.